DISTRIBUTION AND COMPARISON BETWEEN THE MONONCHS NEMATODES OF THREE HILL DISTRICTS (UKHRUL, CHANDEL AND CHURACHANDPUR) OF MANIPUR - DHANACHLAND, CH.; ROMONI, H. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
A comparison was made between the mononchs nematodes found in three hill districts of Manipur. The most commonly occurring nematode species are namely Mylonchulus mulveyi, M. index, Parahadronchus shakili, P andamanicus and Iotonchus parabasidontus. Mononchus truncatus, Prionchulus muscorum, P. ukhrum, Clarkus elongatus, Parahadronchus siroii, Mylonchiulus indistinctus, Mjapanicus and M cassicus are found only in Ukhrul district while Coomansus conoidus, C. venezolanus, Actus baqrus, Mylonchiulus dentatus, M. minor, Cobbonchus impositus, Iotonchus terminus, Parahadronchus andamanicus, P. subhonicus and Hadronchulus denticulus in Chandel district and Mononchus aquaticus, Parahadronchus kangbilus n.sp. and Prionchuloides denticulus n.sp. in Churachandpur district respectively.